2005
DOI: 10.1542/peds.2005-1336
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Sexual Abuse in Children

Abstract: ABSTRACT. This clinical report serves to update the statement titled "Guidelines for the Evaluation of Sexual Abuse of Children," which was first published in 1991 and revised in 1999. The medical assessment of suspected sexual abuse is outlined with respect to obtaining a history, physical examination, and appropriate laboratory data. The role of the physician may include determining the need to report sexual abuse; assessment of the physical, emotional, and behavioral consequences of sexual abuse; and coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
110
1
24

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(142 citation statements)
references
References 33 publications
6
110
1
24
Order By: Relevance
“…The large family structure, substance use, divorce in family, low educational level and low income level are important factors affecting the incidence of incest [2,12,22]. Factors such as substance use, divorced family structure, and low income level were couldn't be evaluated and these are the limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The large family structure, substance use, divorce in family, low educational level and low income level are important factors affecting the incidence of incest [2,12,22]. Factors such as substance use, divorced family structure, and low income level were couldn't be evaluated and these are the limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…21 Data from prepubertal girls are scarce and controversial; its isolated presence does not define CSA. 1 Gardner, et al compared a population of abused and not abused girls and found that it was much more common in the latter group. 22 In our study, Gardnerella vaginalis was isolated in 9.1% of patients.…”
Section: 7mentioning
confidence: 99%
“…1 G e n i t a l e x a m i n a t i o n i s considered a major element when examining a girl victim of abuse. Standards for terminology and classification schemes of physical findings have been established in several publications for the purpose of establishing a relation to the diagnosis of CSA, [2][3][4] and have become a useful diagnostic tool in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Çocukluk dönemi cinsel istismarlarının bir kısmını çocuğun aile içindeki cinsel istismarı olan ensest oluşturmaktadır. Toplumsal olarak önemli bir konu olmasına rağmen göz ardı edilmesi, yokmuş gibi davranılması nedeniyle Dünya Sağlık Örgütü bu sorunu sessiz olarak işleyen sağlık aciliyeti olarak tanımlamıştır (1)(2)(3)(4)(5).…”
unclassified
“…Ensestin varlığını ve ensestin çocuğa yönelik cinsel saldırı olduğunu kabul etmek, ensest karşısında iyi işleyen bir sistemin geliştirilebilmesi için vazgeçilmez noktalardır (1)(2)(3)(4)(5)(6)(7). Ensest konusunda Türkiye›de az sayıda çalışma bulunması nedeniyle Zonguldak ilinde ensest olayının özelliklerini anlayabilmek amacıyla Mahkeme veya Savcılıklardan BEÜ Tıp Fakültesi Hastanesi'ne gönderilen olgular üzerinde değerlendirme yapılmıştır.…”
unclassified